Why are we all women? An exploratory approach on the incidence of gender mandates in the formative experience of students of a primary education teaching staff (Praxis Educativa, 2021)
Various investigations have addressed the historical process of feminization of teaching, emphasizing the production of hegemonic meanings or gender mandates that it has implied. In this article we will propose initial reflections on the incidence of these senses in the formative experiences of students of primary education teachers. To do this, we will analyze the discourses from which the students define the teaching profession and the ways in which hegemonic senses about gender are approached in certain training contexts. Based on the analysis carried out, we propose that, although there are “traces” of feminization mandates in different contexts that make up the formative experience of the students, they are in tension with other approaches, causing ruptures. The methodological approach was carried out from an ethnographic approach in a Higher Institute of Teacher Training in a town in the center of the Province of Buenos Aires (Argentina).
Keywords: education; teacher training; feminization; formative experiences; gender.